Perioperative challenges following management of spontaneous hepatic rupture in a parturient with severe pre-eclampsia – A case report - Keevan Singh; Randall Carvalho; Allan Tinne; Vishal Bahall; Lance De Barry; Steven Sankar (Case Reports in Women's Health, 2023)
Spontaneous hepatic rupture in pregnancy (SHRP) is a rare but often fatal condition associated with pre-eclampsia or HELLP (haemolysis, elevated liver enzymes, low platelets) syndrome. SHRP is linked to significant maternal and perinatal morbidity and mortality, and maternal complications can extend past the initial intraoperative period. This case report describes the challenging perioperative course of a 35-year-old woman with SHRP. She underwent five laparotomies during a prolonged and complicated course in the intensive care unit. Despite these challenges, maternal and fetal outcomes were good. This case report serves to highlight key perioperative multidisciplinary issues in the care of these patients.